Embodied cognition and social consumption: Self‐regulating temperature through social products and behaviors. Issue 2 (27th September 2013) - Lee, Seung Hwan (Mark); Rotman, Jeff D.; Perkins, Andrew W.
Abstract: Extant embodied cognition research suggests that individuals can reduce a perceived lack of interpersonal warmth by substituting physical warmth, and vice versa. We suggest that this behavior is self‐regulatory in nature and that this self‐regulation can be accomplished via consumptive behavior. Experiment 1 found that consumers perceived ambient temperature to be significantly lower when eating alone compared to eating with a partner. Experiment 2 found that consuming a cool (vs. warm) drink led individuals to generate more socially‐oriented attributes for a hypothetical product. Experiment 3 found that physically cooler individuals desired a social consumption setting, whereas physically warmer individuals desired a lone consumption setting. We interpret these results within the context of self‐regulation, such that perceived physical temperature deviations from a steady state unconsciously motivate the individual to find bodily balance in order to alleviate that deviation.